COMPREHENSIVE ASSESSMENT OF DENTISTS KNOWLEDGE AND AWARENESS TOWARDS SURGICAL TEMPLATE USED IN DENTAL IMPLANT THERAPIES: A QUESTIONNAIRE BASED RESEARCH STUDY - Garhnayak, Lokanath; Dhal, Angurbala; Garhnayak, Mirna; Dev, Shruti; Kar, Aswini Kumar; Hota, Sadananda (International Journal of Psychosocial Rehabilitation, 2020)
As a proven fact we know that treatment planning for implant that involves anatomical factors and prosthetic needs is mandatory to ensure a predictable rehabilitation. It also diminishes the overall likelihood of known post-treatment complications. The aim of this study was to evaluate the current knowledge and awareness about surgical template among general dental practitioner in an eastern Indian district. Materials & Methods: This study was wholly attempted on a cross sectional ideology. Here, authors have utilized a reframed questionnaire. All questions was selected and adjusted to meet the actual requirement and concept of present study. A total of 150 private dental practitioners of an eastern Indian district, were originally filtered and contacted for the study. Nonetheless, after considering few crucial aspects, this number was lastly reduced to 100. Authors performed the study by close ended questionnaire having questions about the current knowledge and awareness about surgical template. Response was recorded and data was processed statistically to evaluate the real-time knowledge and awareness level. Results: Statistical analysis was done using statistical software ‘Statistical Package for the Social Sciences (SPSS)’. The recorded data was subjected to suitable statistical tests to obtain p values, mean, standard deviation, standard error an 95% CI. P ≤ 0.05 was considered as statistically significant. 89 participants believe that current dental syllabus is inadequate about the concepts of implant surgical template. Only 15 dentists have participated in any CDE/ Webinar/Demo/Hands-On on implant surgical template. 62 dentists think that usage of implant surgical template must be made compulsory for all dental clinics and hospitals. 42 dentists think that dental implant surgical template possibly will be proved as an definitive tool in implant dentistry and related researches. Only 10 dentists have actually used surgical template at their clinic/hospital. Conclusion: Within the limitations of the study authors concluded that dentists Knowledge and awareness about implant surgical template was at moderate levels.